Students’ perspectives on climate change—unveiling gender–interest associations in climate change beliefs - Höhnle, Steffen; Velling, Hanna; Schubert, Jan Christoph (International Research in Geographical and Environmental Education, 2024)
Climate change is one of humanity’s key problems. Younger generations’ beliefs about and perceptions of climate change are thus of particular importance, as these generations have to tackle the problem in the present and will have to do so even more in the future. Against this background, 4627 high school students in the federal state of Bavaria in Germany were surveyed in a quantitative questionnaire-based study. The analysis shows high values and gender differences for the four general climate change beliefs examined: (1) general perception of climate change as a problem, (2) possible solutions to the problem, (3) contributions to climate protection, and (4) effects on one’s own home. However, mediation analyses suggest that differences are more complex and are to some extent connected to gender differences in interest in climate change.<br
Keywords: beliefs; climate change; climate change; education; geographic education; interest; students